The Effect of Application Development, Data Security, and Infrastructure Availability on Cost Savings and Company Economic Performance - Susilawati, Made; Vandika, Arnes Yuli; Lesmana, Tera (West Science Information System and Technology, 2024)
This study examines the impact of application development, data security, and infrastructure availability on the economic performance and cost savings of companies in Indonesia. Utilizing a quantitative research design, data were collected from 180 companies across various industries using a structured questionnaire. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) 3. The results indicate that all three factors—application development, data security, and infrastructure availability—positively and significantly influence economic performance and cost savings. Infrastructure availability emerged as the most influential factor, underscoring its critical role in supporting technological advancements and efficient operations. These findings provide valuable insights for business leaders and policymakers, emphasizing the importance of strategic investments in technology to enhance financial outcomes and competitiveness in the Indonesian market.